THE PHENOMENON OF SYNONYMY IN MILITARY TERMS - Xidirova Sevara Komiljon qizi (Journal Park Publishing, 2024)
This article explores the intriguing phenomenon of synonomy within the realm of military terminology. Synonomy, the existence of multiple terms conveying similar meanings, is a pervasive feature in the language of warfare. By delving into various examples and contexts, the article elucidates the causes and consequences of synonomy in military lexicon, shedding light on its implications for communication, strategy, and operational effectiveness. Furthermore, it examines how synonomy reflects broader aspects of military culture, history, and organizational dynamics.
Keywords: synonomy, military terminology, language of warfare, communication, strategy, operational effectiveness, military culture, organizational dynamics.